PENGARUH PRODUCT DIVERSITY, HEDONIC VALUE DAN UTILITARIAN VALUE TERHADAP KEPUTUSAN PEMBELIAN PRODUK TAS LES CATINO DI KABUPATEN PONOROGO - Aurelia, Shalsa Fadela; Fery Setiawan; Riawan (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to examine the influence of Product Diversity, Hedonic Value, and Utilitarian Value on Purchase Decisions of Les Catino bag products in Ponorogo Regency. The development of the fashion industry, particularly in bag products, has driven consumers to consider not only functional aspects but also emotional and social factors in their purchasing decisions. This research employs a quantitative method with a survey approach, utilizing questionnaires distributed to 90 respondents through accidental sampling technique. The data were analyzed using multiple linear regression analysis. The results indicate that all three independent variables Product Diversity, Hedonic Value, and Utilitarian Value have a positive and significant effect on Purchase Decisions. Product variety, enjoyable shopping experiences, and the functional benefits offered are essential factors influencing consumers’ decisions to purchase Les Catino bags. These findings are expected to serve as a reference for companies in formulating more effective marketing strategies to strengthen brand positioning in the local market. Keywords : Product Diversity, Hedonic Value, Utilitarian Value, Purchase Decision